Impaired Spatial Memory and Enhanced Habit Memory in a Rat Model of Post-traumatic Stress Disorder - Goodman, Jarid; McIntyre, Christa K. (Frontiers in Pharmacology, 2017)
High levels of emotional arousal can impair spatial memory mediated by the hippocampus, and enhance stimulus-response (S-R) habit memory mediated by the dorsolateral striatum (DLS). The present study was conducted to determine whether these memory systems may be similarly affected in an animal model of post-traumatic stress disorder (PTSD). Sprague-Dawley rats were subjected to a “single-prolonged stress” (SPS) procedure and one week later received training in one of two distinct versions of the plus-maze: a hippocampus-dependent place learning task or a DLS-dependent response learning task. Results indicated that, relative to non-stressed control rats, SPS rats displayed slower acquisition in the place learning task and faster acquisition in the response learning task. In addition, extinction of place learning and response learning was impaired in rats exposed to SPS, relative to non-stressed controls. The influence of SPS on hippocampal spatial memory and DLS habit memory observed in the present study may be relevant to understanding some common features of PTSD, including hippocampal memory deficits, habit-like avoidance responses to trauma-related stimuli, and greater likelihood of developing drug addiction and alcoholism.